Mutations in ATP2A2, encoding a Ca2+ pump, cause Darier disease. - Sakuntabhai, A; Ruiz-Perez, V; Carter, S; Jacobsen, N; Burge, S; Monk, S; Smith, M; Munro, C; O'Donovan, M; Craddock, N; Kucherlapati, R; Rees, J; et al. (1999)
Darier disease (DD) is an autosomal-dominant skin disorder characterized by loss of adhesion between epidermal cells (acantholysis) and abnormal keratinization. Recently we constructed a 2.4-Mb, P1-derived artificial chromosome contig spanning the DD candidate region on chromosome 12q23-24.1. After screening several genes that mapped to this region, we identified mutations in the ATP2A2 gene, which encodes the sarco/endoplasmic reticulum Ca2(+)-ATPase type 2 isoform (SERCA2) and is highly expressed in keratinocytes. Thirteen mutations were identified, including frameshift deletions, in-frame deletions or insertions, splice-site mutations and non-conservative missense mutations in functional domains. Our results demonstrate that mutations in ATP2A2 cause DD and disclose a role for this pump in a Ca(2+)-signalling pathway regulating cell-to-cell adhesion and differentiation of the epidermis.